Sense of Home : The Art of Richard Stout - Edwards, Katie Robinson, 1964-; Reaves, Linda J.; Reaves, William E. (Book collections on Project MUSE., 2017)
Richard Stout's legacy as an artist is broad, deep, and firmly moored to his Texas Gulf Coast origins. Born in Beaumont in 1934, he has been painting, sculpting, and teaching in Houston since 1969, in the process creating both an influential body of work and a committed national and international following among artists and collectors. Stout's oeuvre, encompassing figurative works, abstract expressionism, and a structuralism almost architectural in its geometric precision, has found its place in major museum and private collections in Texas, nationally, and internationally. His exhibitions have appeared in most major American cities and have traveled to Europe, Australia, and Asia. In this, the first retrospective study of a career spanning one of the most tumultuous and formative periods in Texas art, William E. Reaves and the volume contributors offer a meticulously researched, critical examination and assessment of the artist's evolution in style and approach. Richly illustrated with representative paintings and sculptures from throughout Stout's career, the book also provides a comprehensive biographical background, illuminating in multiple dimensions the life and work of one of Texas' most significant contemporary artists.